A 7 years old girl with abdominal lump and per-vaginal bleeding - A rare presentation of Hypothyroidism - Roy, Nibedita; Nahar, Kamrun; Begum, Badrunnesa; Beg, Ayesha; Dhar, Sabita; Sarker, Uttam Kumar; Akter, Fouzia; Roy, Joydip; Chakrabarty, Reemi (Community Based Medical Journal, 2014)
Hypothyroidism is a common endocrine disorder resulting from decreased secretion of thyroid hormone. The diagnosis of hypothyroidism is suggested from the clinical and laboratory findings. Its occurrence in childhood is rare. Here we present a case report on this disease with rare presentation of abdominal lump and pervaginal bleeding in childhood. A 7 years old girl admitted in tertiary level hospital with abdominal lump and irregular per vaginal bleeding. Abdominal swelling was gradually increasing in size & associated with lower abdominal pain for last 5 months. On examination the girl was moderately anaemic, mildly oedematous, distended lower abdomen and a mass in left iliac region. Her thyroid function test, serum FSH, serum LH, serum Prolactin was done and high FSH, LH, Prolactin levels were found. USG of lower abdomen revealed bulky uterus and bilateral ovarian cysts. MRI of Brain showed feature of pituitary microadenoma. Finally the patient was diagnosed as primary hypothyroidism and bilateral follicular ovarian cyst with pituitary adenoma developed as its consequence. The case is reported for clinical awareness & to share our experience. CBMJ 2014 July: Vol. 03 No. 02 P: 41-44